ORGANIZATION OF THE LESSON PROCESS ON THE BASIS OF PERSONALITY-ORIENTED EDUCATIONAL TECHNOLOGIES (World Bulletin of Social Sciences, 2023)
This article will talk about the content of 4 K competencies in the organization of the course process on the basis of a new approaches in the educational system. Personality-oriented educational technologies the emergence of interaction of the personality of a modern teacher by working cooperatively on the personality of a student, in the process of acquiring new knowledge of them, creativity and critical thinking are formed. Also, new approaches to the educational system will dwell on the fact that educational paradigms are a theory that determines the construction of the educational process and direct educational practice
Keywords: educational technologies; 4 K competency approach; student